Effectiveness of Using Emo Demo Methods and Demonstration Methods on Knowledge of Mothers of Stunting Together in Porong Puskesmas, Sidoarjo - Dian Rahma Sania; Ani Intiyati; Nur Hatijah; Juliana Christyaningsih (Politeknik Kesehatan Kemenkes Surabaya, 2023)
One of the factors that causes stunting is the mother's knowledge, so that the mother is approached using counseling. The aim of the study was to determine the difference in the effectiveness of using the emo demo method and the demonstration method on changing the knowledge of stunting mothers at the Porong Sidoarjo Health Center. This type of research is pre-experimental with the type of one group pretest-posttest. The emo demo and demonstration methods each have 10 samples. Data analysis will be carried out by the Dependent T-test. The use of the emodemo and demonstration methods is considered effective in changing the knowledge of stunting mothers with a significant difference in pretest-posttest scores indicating that the emodemo method has a p-value of 0.000 and demonstration has a p-value of 0.002. However, from the comparison of the two methods, it does not have a significant significance value, showing a p-value > 0.05. Emo demos and demonstrations are effective in changing mother's knowledge, but there is no significant difference in changing mother's knowledge.